The Synergistic Cytotoxic Effects of GW5074 and Sorafenib by Impacting Mitochondrial Functions in Human Colorectal Cancer Cell Lines - Hu, Je-Ming; Chang, Yung-Lung; Hsieh, Cheng-Chih; Huang, Shih-Ming (Frontiers in Oncology, 2022)
Colorectal cancer (CRC) ranks third in the United States for incidence or mortality. Surgical resection is the primary treatment for patients at an early stage, while patients with advanced and metastatic CRC receive combined treatment with chemotherapy, radiotherapy, or targeted therapy. C-RAF plays a key role in maintaining clonogenic and tumorigenic capacity in CRC cells and it might be a potential therapeutic target for CRC. Sorafenib is a popular oral multi-kinase inhibitor, including a B-RAF inhibitor, that targets the RAF-MEK-ERK pathway. Sorafenib, as a single agent, has tumor-suppressing efficacy, but its clinical application is limited due to many complex drug resistance mechanisms and side effects. GW5074 is one of the C-RAF inhibitors and has the potential to enhance the efficacy of existing cancer chemotherapies. In this study, we investigated whether the combination of sorafenib with GW5074 could reduce the dosage of sorafenib and enhance its tumor-suppressive effect in two CRC cell lines, HCT116 and LoVo cells. Our findings demonstrate that GW5074 can potentiate the cytotoxicity of sorafenib and dramatically reduce the half-maximal inhibitory concentration (IC50) dose of sorafenib from 17 and 31 µM to 0.14 and 0.01 µM in HCT116 and LoVo cells, respectively. GW5074, similar to sorafenib, suppressed the cellular proliferation and induced cellular apoptosis and cytosolic ROS, but had no further enhancement on the above-mentioned effects when combined with sorafenib. The synergistic effects of GW5074 and sorafenib were mainly found in mitochondrial functions, including ROS generation, membrane potential disruption, and fission–fusion dynamics, which were examined by using the flow cytometry analysis. In summary, the C-RAF inhibitor GW5074 might potentiate the cytotoxicity of the B-RAF inhibitor sorafenib mediated through mitochondrial dysfunctions, suggesting that GW5074 potentially serves as a sensitizer for sorafenib application to reduce the risk of drug resistance of CRC treatment. Our findings also provide novel insights on using C-RAF inhibitors combined with sorafenib, the current CRC therapeutic drug choice, in CRC treatment.